PENGEMBANGAN DESAIN TUGAS PENALARAN MATEMATIS MELALUI COUNTER EXAMPLE UNTUK MENUMBUHKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Siti Zulaiha; Sugiatno Sugiatno; Yulis Jamiah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research is background by the lack of integration between mathematical reasoningand students' critical thinking skills in mathematics. The facts obtained from interviewsshowed that the assignments were given to students still use the questions contained inthe books, so that students have not fully used their reasoning to think critically. A goodassignment should be a task designed with attention to student response patterns so thatepistemological obstacles that often arise can be overcome. This study aims to develop amathematical reasoning assignment design by providing a counter example (CE), withCE students can explore related assignments so that they can foster students' criticalthinking skills. This research was didactical design research which involved six studentsusing written tests and interviews. The results of the study revealed that the assignmentdesign with CE could reveal the presence of learning obstacle that hindered students'critical thinking skills and able to overcome the learning obstacle. The conclusion is thatstudents' critical thinking skills have developed after being given a mathematicalreasoning design through the provision of CE, this is shown by the post-test average score(62.56) which is higher than the pre-test average (15.03).Keywords: Task Design, Counter Example, Critical Thinking Skills, MathematicalReasoning